Heritage and its Distribution in Practice in Religious Courts - Haeratun, Haeratun; Surayya, Ita; Fatahullah, Fatahullah; Jamaluddin, Jamaluddin (Jurnal Pengabdian Pancasila (JPP), 2024)
Trust for wealth, if not implemented properly, can become a source of disharmony in human life in society. Interactions between poor community members can escalate into hostile attitudes and eventually disputes can occur. Islamic sharia has stipulated the rules of inheritance as best as possible with the rules of wealth clearly and fairly. This is because Islam recognizes a person's ownership of property, both male and female, through a path that is justified by the Shari'a, just as Islam recognizes the transfer of something that a person owns during his life to his heirs after death, whether the heirs are male or female, without distinguishing between children and adults. The noble Qur'an has explained the laws of inheritance, the circumstances of each heir with a sufficient explanation, whereby no one among mankind is exempt from the share or limitation of inheritance. For the Qur'an is its basis in determining the law and its part. And very few are set on the basis of Sunnah and Ijma'. And not found in the Shari'a, the laws explained by the Qur'an are as clear and detailed as these inheritance laws. Indeed, Islam's attention to the matter of inheritance is an extraordinary concern, so the noble Qur'an privileges its explanation with the clearest explanation and not vague.